Estimation of Surface Runoff for Mahatma Phule Krishi Vidyapeeth Central Campus, Ahilyanagar, Maharashtra, Using Remote Sensing and Geographical Information System - Nandgude, S. B.; Ganachari, H. S.; Shinde, S. S.; More, D. D.; Chavan, M. D.; Kamble, B. S.; Patil, V. V.; Khapke, O. N. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the month of December to May, 2024 at the department of Soil and Water Conservation Engineering, Dr. Annasaheb Shinde College of Agricultural Engineering and Technology, Rahuri, Maharashra, India for watershed planning and Management study at Mahatma Phule Krishi Vidyapeeth Central Campus, Ahilyanagar, Maharashtra. This study estimated annual run-off in 2021 for a 475 ha micro-watershed within the Mahatma Phule Krishi Vidyapeeth (MPKV) Central Campus (West), situated between 19°19’ to 19°22’ N latitude and 74°36’ to 74°40’ E longitude, using the Soil Conservation Service – Curve Number (SCS-CN) method integrated with ArcGIS 10.5. Essential thematic layers, including stream order, digital elevation model (DEM), hydrologic soil group (HSG), curve number (CN), and land use/land cover (LULC) maps, were generated to support spatial analysis and runoff computation. The weighted curve numbers determined for antecedent moisture conditions I, II, and III were 53.53, 73.28, and 86.32, respectively. Results showed that the watershed experienced an annual surface runoff depth of 278.97 mm, corresponding to 28.86% of the 966.40 mm total rainfall during 2021. The derived runoff estimates provide a critical baseline for designing water-harvesting and soil-conservation structures. Furthermore, these pre-development runoff values serve as a reference for evaluating the effectiveness and impact of future soil and water conservation interventions within the watershed.